Hungurvaka; sive, Historia primorum quinqve Skalholtensium in Islandia episcoporum, Pals biskups saga (Hafniae, A. H. Godiche, 1778)
Edited and translated into Latin by Jón Ólafsson (Hypnonesius) Added t.-p. in Icelandic. Mode of access: Internet.